Arranjos curriculares e repercussões ao trabalho docente em educação física a partir da reforma do ensino médio na rede de ensino pública estadual de Santa Maria/RS - Pastorio, Anapaula (2024)
The knowledge that forms the curriculum is permeated by meanings and power relations that carry political and ideological intentions. In line with the BNCC proposal, in 2017, the High School Reform (REM) was approved through Law 13,415/17, which proposes a curricular reorganization, eliminating essential curricular components of Basic Education to implement formative itineraries (linked to technical training for the job market), causing the impoverishment of the content of this stage of education. In addition to the student losses due to early specialization, and also the encouragement of public-private partnerships, the REM increased the disparity in the degree of importance attributed to curricular components, reducing the workload of those historically considered less important, such as physical education. From this perspective, the research sought to understand the repercussions of the curricular arrangements of the High School Reform for the teaching work of Physical Education in the public education system of the state of Santa Maria / RS. To this end, within the scope of the qualitative approach and using the Case Study methodology, we sought to understand, in the context of practice, two schools in the state public network of Santa Maria/RS participating in the government program Escola Melhor: Sociedade Melhor, in order to elucidate the curricular and teaching work issues modified by REM. The study used two techniques, documentary analysis (Law 13,415/17, BNCC-EM/2018, Gaucho Curricular Reference, the Curricular Matrices - Ordinance No. 350/2021, Ordinance No. 282/2022 and Ordinance No. 551/2023 - and the Political Pedagogical Projects of the institutions researched) and the semistructured interview with the managers and Physical Education teachers of these schools. Data analysis was based on Discursive Textual Analysis (MORAES; GALIAZZI, 2016), the context of the Policy Cycle practice (BOWE; BALL; GOLD, 1992) and the Theory of Action (BALL; MAGUIRE; BRAUIN, 2016). In the discussion of the results, it was observed, based on the context of the practice, the lack of teaching autonomy, the performative process, materialized through demands and blaming of teachers, and the precariousness, imposed especially by the pulverization of components to be assumed under a supposed flexibility of the curriculum. Consequently, it was noticed that the REM has been motivating the bureaucratization and overload that result, above all, in the intensification (DAL ROSSO, 2008) of teaching work. Regarding the specificities of the Physical Education component, the educational losses caused by the reduction of the component's workload are evident, in which the teacher is unable to achieve his teaching objectives with the students, asserting the difficulty in demonstrating the importance of the area. Furthermore, it is clear the precarious teaching conditions that the 2024 Curricular Matrices Guide imposed by relegating non-attendance to Physical Education in Nighttime High School, crediting the component only with the distance modality. Even so, it was possible to understand through this research that teachers continue to reinvent themselves and be resilient, seeking through interpretations and translations (BALL; MAGUIRE; BRAUIN, 2016), to break the standardized curriculum that prevents the individualization of the teaching and learning process, to bring the content closer to the reality of students in a way that makes sense to them. Finally, we hope that this study gives the necessary visibility to the damage that the Reform has caused to teaching work and the curriculum of public schools, so that the curricular policy can be rethought through a broad debate in which teachers and students are heard, but in addition to being listened to, their opinions are respected.